The efficiency of developing coordination skills in figure skaters during the initial training phase - Babushkina L.E. ,; Matveenko D.I. ,; Tuzova E.N. ,; Mirzoev V.I. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to enhancing the coordination skills of young skaters aged 6-8 years during the initial training phase to enhance their technical proficiency. Methods and structure of the study. The pedagogical experiment was carried out from June to April of the 2023-2024 educational and training year. The experiment involved figure skaters 6-8 years old with the norm of a young skater and 2-3 youth categories of the State Budgetary Institution of Educational Institution of the Republic of Moldova, Secondary School «Academy of Figure Skating» under the guidance of the Honored Coach of Russia, head coach of the Republic of Mordovia, L.N. Yakovleva. During the year, sets of exercises developed for the experiment for training figure skaters were introduced, and a number of motor and medical-biological tests were carried out to determine the level of development of coordination abilities and the state of the vestibular analyzer. Results and conclusions. The outcomes of the development of coordination skills in figure skaters during the initial training phase, before and after the experiment described in the article, show a positive trend. There was a substantial enhancement in the development of coordination abilities in figure skaters aged 6-8 years during the initial training phase, which confirms the efficacy of the proposed set of exercises. The research of several authors is examined in the context of the topic, and a set of exercises is practically suggested based on the analysis.